(untitled) (Applied Biological Research, 2023)
Mountainous regions are more sensitive to climate change so the plant biodiversity along elevation faces many obstacles than just competition. Thus, many plant species in these ecosystems make slight alteration in their ranges for survival. In the mountainous areas of North-Western Himalayan region, Sambucus wightiana is one of the major subshrub species that has begun to extend its distribution. Despite its wide distribution across the North-Western Himalaya, ncomprehensive and reliable published study detailing the phytosociology of S. wightiana is available. Therefore, in the present study, the phytosociological relationships of S. wightiana in the Sonamarg area was studied. The study area was divided into 11 altitudinal bands, from lowest thighest sampling locations. The plant species associated and not associated with S. wightiana at each altitudinal band were collected using standard taxonomic techniques. A total of 76 plant species belonging to 35 families were found along the altitudinal gradient from 1723 to 2858 m masl. The study clearly revealed the relationship of a few plant species with S. wightiana and the absence of other species in S. wightiana plots. The findings suggest that S. wightiana has developed distinct phytosociological connections, which may alter because of the expected climate change as most of the species may exhibit distinctive responses to mountain warming.